PENGARUH HIGH PERFORMANCE WORK PRACTICE (HPWP) TERHADAP JOB PERFORMANCE PADA FRONTLINER BANK - Monica Amani Ihdaryanti; Mutiara S. Panggabean (Jurnal Manajemen dan Pemasaran Jasa, 2014)
Generally High Performance Work Practice (HPWP) is a part of management human resources.The objectives of this research are getting and analyzing the effect of HPWPs with Job Satisfaction;HPWPs with Organizational Commitment; Job Satisfaction with Organizational Commitment;Job Satisfaction with Job Performance; and Organizational Commitment with Job Performance.The total of sample in this research is 100 respondents which are as Front liner BNI and Mandiri.The result of this research concluded that has effect between HPWPs with Job Satisfaction;there is no positive correlation between HPWPs with Organizational Commitment; there is positivecorrelation Job Satisfaction with Organizational Commitment; there is positive Job Satisfactionwith Job performance; there is positive correlation Organizational Commitment with JobPerformance.Keywords: HPWP, Job Performance, Frontliner Bank